Wiley Encyclopedia of Composites 2012
DOI: 10.1002/9781118097298.weoc061
|View full text |Cite
|
Sign up to set email alerts
|

Cutting and Machining of Polymer Composites

Abstract: This article discusses the phenomena of machining of fiber‐reinforced polymer composites by conventional and nonconventional means. First, the underlying principles of machining by a wedge‐shaped tool are discussed and the application of these principles to the distinctive structure of fiber‐reinforced polymers is delineated. The influence of fiber orientation on the chip formation mode, cutting forces, and surface roughness is explained. Machinability of composites in terms of tool wear and surface roughness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
1
20
0
5
Order By: Relevance
“…It is found that a large helix angle will result in thick and continuous chips compared to a low helix angle, as a result of high shearing force. Figure 8 shows chip formation for a large helix angle cutting tool which indicates the polymeric softening as a result of localized heat on cutting zone (Sheikh-Ahmad, 2009;Yang et al, 2003). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that a large helix angle will result in thick and continuous chips compared to a low helix angle, as a result of high shearing force. Figure 8 shows chip formation for a large helix angle cutting tool which indicates the polymeric softening as a result of localized heat on cutting zone (Sheikh-Ahmad, 2009;Yang et al, 2003). …”
Section: Resultsmentioning
confidence: 99%
“…Large rake angles produced thin and continuous chip morphology at the side machining surface which shows that the high shear stress occurred at the PEEK polymer as shown in Figure 6. The high shear stress increased the strain rate of the PEEK polymer due to the behavior of thermoplastic properties, which exhibited high elastic strain proportional with the stress increment (Fried, 2003;Sheikh-Ahmad, 2009). Figure 6.…”
Section: Experimental Design and Setupmentioning
confidence: 99%
“…Ta metoda jest jednak znacznie droższa ze względu na koszty inwestycyjne i eksploatacyjne. Ponieważ polimery są izolatorami elektrycznymi, niemożliwe jest zastosowanie cięcia plazmą bądź EDM [8]. W celu określenia, która z metod perforacji najlepiej nadaje się w przypadku pasów kompozytowych, krótko scharakteryzowano pozostałe metody.…”
Section: Metody Perforacji Pasów Kompozytowychunclassified
“…Strategią zapobiegania delaminacji jest zwiększenie sztywności dolnej warstwy dzięki zastosowaniu płyty podporowej lub zmiennego posuwu roboczego. Innym defektem wiercenia w kompozytach może być owalność otworów związana z orientacją włókien w strukturze materiału [8,[13][14][15].…”
Section: Metody Perforacji Pasów Kompozytowychunclassified
See 1 more Smart Citation